2013
DOI: 10.3329/bja.v9i2.15281
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Assessment of Nutritional Status of Bangladeshi Pregnant Women and Weight of their Newborns

Abstract: DOI: http://dx.doi.org/10.3329/bja.v9i2.15281 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.101-105

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Thus mothers of normal birth weight neonates were also significantly taller and heavier than their low birth weight counterparts [ 29 ]. This is similar to the findings of Momen et al [ 17 ] in their study titled Anthropometric assessment of nutritional status of Bangladeshi pregnant women and weight of their newborns , conducted in Bangladesh. In their study they found a positive association between the weight of mothers and that of their neonates.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus mothers of normal birth weight neonates were also significantly taller and heavier than their low birth weight counterparts [ 29 ]. This is similar to the findings of Momen et al [ 17 ] in their study titled Anthropometric assessment of nutritional status of Bangladeshi pregnant women and weight of their newborns , conducted in Bangladesh. In their study they found a positive association between the weight of mothers and that of their neonates.…”
Section: Resultssupporting
confidence: 91%
“…Thus a weight gain is popularly associated with normal birth weight whereas a maternal weight loss is associated with low birth weight, among others [ 14 ]. Some studies have been conducted into the relationship between maternal anthropometric measurements, other maternal factors and birth weight [ 11 , 14 17 ].…”
Section: Introductionmentioning
confidence: 99%